Acetabular reconstruction using a ?Cone Cup? prosthesis in a series of 13 patients - Klopper, Schalk (Division of General Surgery, 2024)
Background Endoprosthetic reconstruction of major pelvic bone loss in oncology and revision arthroplasty surgery is associated with high complication rates. However, comparative data for reconstructive methods are limited. We present short-term clinical, radiological, and functional outcomes of the implantcast MUTARSâ LUMICâ prosthesisfor acetabular reconstruction after major pelvic bone resection orloss. Methods Retrospective folder review from December 2019 to June 2022. Minimum follow up was 12 months. The inclusion criterion was all patients who underwent acetabular reconstruction with the implantcast MUTARSâ LUMICâ cone cup prosthesis. Results Thirteen patients were included in the study. The indication for pelvic resection was a primary bone tumour in five patients, metastatic bone disease in five and failed arthroplasty in three. Complications included 2 patients with dislocation, 3 with infection, and 1 with both. The overall complication rate was 46%. Median MSTS scores at 12 months assessed in 8 patients was 20.75 of 30 points. Conclusion Our results are in agreement with other series, highlighting the problems of instability and deep infection. Patients without complications had an acceptable functional outcome.